2007
DOI: 10.1111/j.1365-2702.2006.01382.x
|View full text |Cite
|
Sign up to set email alerts
|

The association between caregiving satisfaction, difficulties and coping among older family caregivers

Abstract: Reinforcing the health-promoting qualities in caregivers who are not feeling well, with women as a particularly vulnerable group, may restrict unnecessary suffering for both the caregiver and the person cared for.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
72
2
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(81 citation statements)
references
References 28 publications
4
72
2
3
Order By: Relevance
“…H e a l t h p r o f e s s i o n a l s h a v e t o anticipate the needs of caregivers and foresee the development of personal situations (15) . The CASI i n s t r u m e n t h a s b e e n i n c r e a s i n g l y u s e d i n caregiving studies, providing important reflections for intervention (16)(17) , but it is still mostly used in dementia situations. We strongly advocate that it …”
Section: Discussionmentioning
confidence: 99%
“…H e a l t h p r o f e s s i o n a l s h a v e t o anticipate the needs of caregivers and foresee the development of personal situations (15) . The CASI i n s t r u m e n t h a s b e e n i n c r e a s i n g l y u s e d i n caregiving studies, providing important reflections for intervention (16)(17) , but it is still mostly used in dementia situations. We strongly advocate that it …”
Section: Discussionmentioning
confidence: 99%
“…Qualitative interviews show that informal carers may also experience feelings of appreciation, increased affinity with the care recipient, growth, and satisfaction in their role as caregiver, and that these rewards can co-exist with high levels of stress. [10][11][12] More quantitative research is thus needed on variables such as self-esteem, mastery, and life satisfaction, which may be posited as enhanced by the experience and even the challenges of caregiving. 13 Psychological, or subjective, well-being can be conceptualized as comprising both a cognitive component, that is, cognitive well-being (satisfaction with life), and an affective component, that is, affective well-being.…”
Section: Introductionmentioning
confidence: 99%
“…Also, research indicates that women are in better physical health and maintained higher levels of socialization outside of caregiving (DiBartolo & Soeken, 2003). However, men were more satisfied with the role of caregiving than women (Broe et al, 1999;DiBartolo & Soeken, 2003;Ekwall & Hallberg, 2007). Ekwall and Hallberg (2007) noted that men were more likely to be experiencing caregiving for the first time compared to women and therefore, experienced more personal growth in the role of family caregiver than women caregivers.…”
Section: Men and Women Caregiversmentioning
confidence: 99%
“…Caring for an elderly family member demands a significant amount of energy from the caregiver placing them at risk for physical and mental health decline as a result from the stress of caregiving (Haley et al, 2004;Proulx & Snyder, 2009). Previous research has indicated that negative effects of family caregiving can be decreased with social support and positive coping behaviors such as problem-focused strategies (e.g., reading about the disease process of the care receiver, Ekwall & Hallberg, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation